2014
DOI: 10.1186/1756-8722-7-40
|View full text |Cite
|
Sign up to set email alerts
|

Argonaute 2 promotes myeloma angiogenesis via microRNA dysregulation

Abstract: BackgroundDysregulated microRNA (miRNA) expression contributes to cancer cell proliferation, apoptosis and angiogenesis. Angiogenesis is a hallmark of multiple myeloma (MM) development and progression. Argonaute 2 (AGO2) protein, a core component of the RNA-induced silencing complex (RISC), can directly bind to miRNAs and mediate target messenger RNA (mRNA) degradation. A previous study showed that AGO2 knockdown suppressed human umbilical vein endothelial cell (HUVEC) growth and tube formation. However, the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 47 publications
(59 reference statements)
1
34
0
Order By: Relevance
“…The observed biological effects of BCP plasma exosomes could be due to the increased miR-92a expression in these vesicles, which we have demonstrated in the current study for the first time. This assumption is supported by previous studies which have shown that the increased level of miR-92a correlates with increased angiogenesis and cell migration activity [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The observed biological effects of BCP plasma exosomes could be due to the increased miR-92a expression in these vesicles, which we have demonstrated in the current study for the first time. This assumption is supported by previous studies which have shown that the increased level of miR-92a correlates with increased angiogenesis and cell migration activity [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 80%
“…A number of previous studies have indicated that miRNAs, being one of the main functional components of exosome cargo, may play a crucial role in cell-to-cell communication and eventually regulate the biological functions of recipient cells. It is known that miR-92a and miR-25-3p are up-regulated in cell lines with enhanced EMT, cell motility, and angiogenesis [ 25 , 26 , 27 , 28 , 29 , 30 ]. Since the miR-16-5p expression was stable and reproducible, it was chosen as an endogenous control to normalize the miRNA expression [ 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, Vickers et al reported that the uptake of miRNA high-density lipoprotein (HDL) in plasma by recipient cells appears to be dependent on a cell-surface HDL receptor named scavenger receptor class B, type I (SRBI) [ 68 ], suggesting a novel possible mechanism for the function of circulating miRNAs on the progression of atherosclerosis or cancer. Currently, several miRNA-binding proteins have been reported to participate in circulating miRNA inter-or extra-cellular communication, such as nucleophosmin1 (NPM1) [ 69 ] and Argonaute2 (Ago2) -1,-2 -3 and -4 [ 16 , 70 72 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, lenalidomide treatment of siCRBN-mediated knockdown cells showed less inhibition in tubule formation (as compared to lenalidomide-treated wild-type cells) following treatment for 18 hours ( Figure 3B). The positive control, CPS49, a well-characterized potent antiangiogenic analog of thalidomide [25][26][27][28] also inhibited lattice formation regardless of CRBN knockdown.…”
Section: Resultsmentioning
confidence: 99%